Rheological, chemical and DSC thermal characteristics of different types of palm oil/palm stearin-based shortenings - Ariffin, Abdul Azis (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2011)
This study was carried out to evaluate the physical and chemical properties of different types of shortenings, formulated by mixing refined, bleached, and deodorized palm oil and palm stearin (PO:PS) in the following ratios: 100:0, 80:20, 60:40, 50:50, 40:60 and 20:80 and 0:100. The properties of experimental and commercial shortenings were investigated using four different analytical techniques, namely high performance liquid chromatography (HPLC), gas chromatography (GC), differential scanning calorimetry (DSC) and controlled stress rheometer. In addition, iodine value (IV) analysis was carried out. The results revealed that the prominent fatty acids in the products were palmitic (44.88-61.91%), oleic (26.24-39.14%) and linoleic (6.13-11.68%). At the same time, triacyglycerols (TAG), such as OOO, OOP and OOS, were found to decrease, while PPO increased due to the increase in the palm stearin content of the shortenings. Higher viscosity and more storage (G′) or loss (G″) modulus properties were noted in the experimental and commercial shortenings containing higher and lower concentrations of palm stearin and palm oil, respectively. Certain parameters such as the onset, peak and endset temperatures (ºC) were detected for both the melting and cooling data. However, increasing the palm stearin concentrations in the samples was shown to have caused increases in the endset temperature and peak height, and vice versa. Thus, chemical and physical properties of the formulated shortenings may influence the quality of baked products.